METAPHORICAL FUNCTIONS OF PHYTONYMS IN FOLK WISDOM AND PROVERBS - Nekboeva Rano Zokirovna (Modern American Journals, 2025)
The aarticle examines how phytonyms function as metaphors within folk proverbs across various cultures. Phytonyms function as reflective instruments that show agricultural heritage along with moral principles and social conduct and natural world perceptions. The research analyzes Uzbek and English proverbs to identify plant metaphors and studies their symbolic meanings and cognitive models and linguistic variations. The study demonstrates that phytonyms represent either strength or elegance or wisdom or peril based on cultural settings. The research enhances knowledge about the connections between metaphorical language and flora and linguistic elements which create traditional worldviews.
Keywords: Phytonyms, metaphor, proverbs, linguoculture, symbolism, ethnolinguistics, folk wisdom